Pengembangan Multimedia Pembelajaran pada Pembelajaran Informatika Kelas VIII di SMP Negeri 1 Kinali - Gusfianora, Fara; Eldarni, Eldarni; Syafril, Syafril; Rayendra, Rayendra (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research aims to produce multimedia learning in informatics subjects using a 4D (four-D) development model which includes four stages, namely define, design, development, and dissemination. In the Development Step, a media validity test was carried out with two media expert validators and one material expert validator, then a practicality test was carried out on 30 junior high school grade VIII students to test the practicality of the multimedia learning developed. The results of the media validity assessment with validator I got a percentage of 94.67 with the category